67.4k views
2 votes
HELP I DONT UNDERSTAND THEIS QUESTIIONS

1 Answer

1 vote

1) f(x)-3


\begin{gathered} f(x)=2x-4 \\ \Rightarrow f(x)-3=2x-4-3 \end{gathered}

Therefore, f(x)-3=2x-4-3

2) f(x-3)


\Rightarrow f(x-3)=2(x-3)-4

Thus, f(x-3)=2(x-3)-4

3) f(-3x)


f(-3x)=2(-3x)-4

Then, f(-3x)=2(-3x)-4

4) -3f(x)


-3f(x)=-3(2x-4)

Hence, -3f(x)=-3(2x-4)

User FlamingLogos
by
5.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.